2018
DOI: 10.1183/13993003.02310-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and comorbidity on risk stratification in idiopathic pulmonary arterial hypertension

Abstract: Recent reports from worldwide pulmonary hypertension registries show a new demographic picture for patients with idiopathic pulmonary arterial hypertension (IPAH), with an increasing prevalence among the elderly.We aimed to investigate the effects of age and comorbidity on risk stratification and outcome of patients with incident IPAH.The study population (n=264) was categorised into four age groups: 18-45, 46-64, 65-74 and ≥75 years. Individual risk profiles were determined according to a risk assessment inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
123
3
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(154 citation statements)
references
References 36 publications
10
123
3
18
Order By: Relevance
“…Registry data show that PAH drugs are widely used in older patients with multiple comorbidities, but little is known about their safety and efficacy in these patients. The present paper by HJALMARSSON et al [6] reinforces this notion by demonstrating absence of substantial clinical improvements in the majority of older IPAH patients receiving PAH therapies. Registry data help to better characterise and understand these patients, but eventually, adequate representation in randomised trials is necessary to determine the best possible care for this increasingly relevant group of patients.…”
Section: Treatment and Treatment Responsesupporting
confidence: 66%
See 2 more Smart Citations
“…Registry data show that PAH drugs are widely used in older patients with multiple comorbidities, but little is known about their safety and efficacy in these patients. The present paper by HJALMARSSON et al [6] reinforces this notion by demonstrating absence of substantial clinical improvements in the majority of older IPAH patients receiving PAH therapies. Registry data help to better characterise and understand these patients, but eventually, adequate representation in randomised trials is necessary to determine the best possible care for this increasingly relevant group of patients.…”
Section: Treatment and Treatment Responsesupporting
confidence: 66%
“…Perhaps the most important clue to the findings by HJALMARSSON et al [6] is a better understanding of how older patients respond to PAH targeted therapies. Such patients were not well represented in PAH studies.…”
Section: Treatment and Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The aging process itself predisposes to vitamin D deficiency due to a progressive decline in the cutaneous capacity to synthetize vitD and reduced exposure to sunlight [56]. This bias may have influenced the results because the five-year survival was reported to be higher in PAH patients aged 18-45 years (88%), while the survival rates were 63%, 56%, and 36% for patients in the groups 46-64, 65-74, and ≥75 years, respectively [57]. However, after adjusting for age, survival still remained significantly different for those with high vs. low levels of total 25(OH)vitD.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 European pulmonary hypertension guidelines propose a multidimensional risk assessment strategy based on nine items and 13 distinct variables in order to predict the estimated 1-year mortality [1,2]. Recently, several large registry studies have shown that simplified tools can be used to predict outcomes and guide treatment decisions [3][4][5][6]. These studies have focused largely on 6-min walking distance (6MWD), World Health Organization (WHO) functional class (FC), right atrial pressure (RAP), cardiac index (CI) and brain natriuretic peptides (BNP or NT-proBNP).…”
mentioning
confidence: 99%